MEASUREMENT OF EFFICIENCY: AN EMPIRICAL OF ISLAMIC STOCK EXCHANGES IN OIC COUNTRIES - Mauizhotul Hasanah; Faris Kurnia Hakim; Sri Herianingrum (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2026)
The efficienct market is one of the benchmarks for investors, because investors need to monitor all information to consider investing decisions. This study aims to measure the level of efficiency in the Islamic stock exchanges of Islamic countries. The data used is secondary data using a sample of 6 Islamic countries that are members of the OIC in the January 2014-December 2018 period. The method used is the Stochastic Frontier Approach (SFA) with an analysis tool, namely the Frontier 4.1 software. The input variable used is Market Capitalization (KP) and Trading Volume (VP), while the output variable used is Individual Market Return (IMR). The results of this study indicate that during the study period there was no stock market that obtained a perfect efficiency value of one. The average result of the technical efficiency value of Islamic stock exchanges in Islamic countries is 0.9706, then based on ƴ of 0.38221 or 38%, it means that this inefficiency value needs to be optimized. . The country with the highest average technical efficiency value was in the UAE at 0.97173 and the country with the lowest average technical efficiency value was Saudi Arabia at 0.96939. Based on the classification of the overall countries operating efficiently, namely the UAE, Indonesia, and Iran, while the less efficient countries are Saudi Arabia, Kuwait, and Qatar.